2018
DOI: 10.2991/j.jegh.2018.08.101
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of 50 Patients with Surgically Treated Cystic Echinococcosis from Basrah Province, Iraq

Abstract: Cystic echinococcosis (CE) is recognised worldwide as a neglected disease of public health concern, particularly in low-and middle-income countries. The objectives of this study were to describe, using a questionnaire survey, the characteristics, attitudes, knowledge, and practices of patients with CE from Basrah Province, Iraq. We interviewed 50 patients, 31 female and 19 male, of whom, 74% originated from rural areas. Approximately half (48%) of the participants reported slaughtering livestock at home for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
1
0
1
Order By: Relevance
“…Our results are similar to the findings of Abdulhameed et al, a study on surgical cases of CE in Iraq, which reported that 72% of the participants had not heard of CE and 57% did not know the mode of transmission of hydatid cysts, even after surgery for the disease [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to the findings of Abdulhameed et al, a study on surgical cases of CE in Iraq, which reported that 72% of the participants had not heard of CE and 57% did not know the mode of transmission of hydatid cysts, even after surgery for the disease [14].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 62.5% of the participants reported slaughtering and butchering at home. Abdulhameed et al reported that around 50% of surgical cases of CE in Iraq performed home slaughtering and butchering [14]. Many studies have 5 Journal of Parasitology Research highlighted the effect of the common practice of slaughtering animals by householders in or near their homes on CE infection [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…La tenencia de perros es un factor de riesgo relevante, sobre todo si no son desparasitados regularmente, la costumbre de mantener contacto estrecho con ellos, la presencia de perros callejeros y especialmente la faena animal en los domicilios con la práctica de alimentar perros con vísceras eliminadas. Finalmente, el desconocimiento de la existencia de la enfermedad y escasa educación sanitaria por los equipos de salud, también son considerados como factores de riesgo [9][10][11][12] . La educación y alfabetización en salud son importantes en el control de las enfermedades desatendidas.…”
unclassified